2013
DOI: 10.1073/pnas.1318018111
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic plug functions as a gate in voltage-gated proton channels

Abstract: Voltage-gated proton (Hv1) channels play important roles in the respiratory burst, in pH regulation, in spermatozoa, in apoptosis, and in cancer metastasis. Unlike other voltage-gated cation channels, the Hv1 channel lacks a centrally located pore formed by the assembly of subunits. Instead, the proton permeation pathway in the Hv1 channel is within the voltage-sensing domain of each subunit. The gating mechanism of this pathway is still unclear. Mutagenic and fluorescence studies suggest that the fourth trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(166 citation statements)
references
References 56 publications
10
150
1
Order By: Relevance
“…While Hv1 is ubiquitously expressed and plays an important role in a number of physiological processes such as the innate immune system, apoptosis, and cancer metastasis, the presence of Hv1 in human spermatozoa was intriguing. Hv1 is not a true ion channel, but rather a strange mix between a transporter and an ion channel without the pore, that provides rapid movement of protons across a lipid bilayer via a voltage-gated mechanism [116][117][118].…”
Section: Mechanisms Of Proton Extrusion From Mammalian Spermmentioning
confidence: 99%
See 3 more Smart Citations
“…While Hv1 is ubiquitously expressed and plays an important role in a number of physiological processes such as the innate immune system, apoptosis, and cancer metastasis, the presence of Hv1 in human spermatozoa was intriguing. Hv1 is not a true ion channel, but rather a strange mix between a transporter and an ion channel without the pore, that provides rapid movement of protons across a lipid bilayer via a voltage-gated mechanism [116][117][118].…”
Section: Mechanisms Of Proton Extrusion From Mammalian Spermmentioning
confidence: 99%
“…Unlike traditional voltage-gated ion channel, Hv1 does not possess a pore domain. Several models for the proton conductance pathway have been proposed [116,117,126]. The "water wire" model [117] proposes the movement of protons via Grotthus mechanism from the intracellular water vestibules to the extracellular vestibule formed by the transmembrane (TM) portions of the channel.…”
Section: Hv1: Principles Of Proton Permeationmentioning
confidence: 99%
See 2 more Smart Citations
“…50 Recently, it has been found that Arg directly associates with the opening and closing of voltage-gated proton channels, which play important roles in various physiological processes, including the innate immune response. 51 Thus, promoting the effect by having more Arg may be counteracted by simultaneously introducing structure instability.…”
Section: Balanced Hydrophobic and Hydrophilic Residue Repeating Sequementioning
confidence: 99%